If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2n + -1 = -15 Reorder the terms: -1 + 2n = -15 Solving -1 + 2n = -15 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 2n = -15 + 1 Combine like terms: -1 + 1 = 0 0 + 2n = -15 + 1 2n = -15 + 1 Combine like terms: -15 + 1 = -14 2n = -14 Divide each side by '2'. n = -7 Simplifying n = -7
| 2m^2+3=53 | | m^2-3=22 | | 200+10=210 | | -4/9x=36 | | a^2+6=48 | | x/0.3=-4.2 | | 6-3x=11+2x | | (-x/8)=1 | | x+86=110 | | (x/4)=12 | | 1/2+r=31/4 | | 1/2+r=3/1/4 | | (-x/10)=13 | | 7-2b=10 | | -24x-6/-2=15 | | 4x+9x+3x=30 | | 5+2y=2y+6 | | 5x^2-7/2x=1/2x+1 | | 5x-3=8+4x | | (x/17)=4 | | x^2/3+2x=1+x | | 6y+2(y-4)=4(y+1)-3 | | (x/17)=2 | | -29=-5b+6 | | (-x/10)=3 | | 5(x-1)-8=2x+3(-3+x) | | -20=10+6r | | x^2/5-3x^1/5+2=0 | | X/9-6=-5 | | -4y-9=2y+9 | | 9+n/6=8 | | 6(8-z)/5=-z |